The inter-relationship between financial characteristics of firms and CEO restricted stock units. - Wee, Yuzhen. (2012)
This paper recognizes the rising popularity of Restricted Stock Units (RSUs) as a long-term incentive tool in retaining competent and well-performing Chief Executive Officers. It strives to examine the influence of seven firm characteristics on firms’ decisions to award RSUs and if so, the quantum awarded. Our findings suggest that firms with lower return on assets and higher leverage are more likely to utilize RSUs as a CEO retention tool. In addition, for firms which award RSUs, we observed a positive relationship between the value awarded and the asset value of the company. Overall, our results support the optimal contracting view that a firm’s compensation scheme is an optimal response to its labor market competition for managerial talents.